PhageWeb – Web Interface for Rapid Identification and Characterization of Prophages in Bacterial Genomes - Sousa, Ailton Lopes de; Maués, Dener; Lobato, Amália; Franco, Edian F.; Pinheiro, Kenny; Araújo, Fabrício; Pantoja, Yan; Costa da Silva, Artur Luiz da; Morais, Jefferson; Ramos, Rommel T. J. (Frontiers in Genetics, 2018)
This study developed a computational tool with a graphical interface that allows the identification of regions of phages through homology searches, clustering of genes, evaluation of G+C content variation, tRNA sites prediction and functional characterization, beyond the integration of phage information by the webservices of other applications. The performance of PhageWeb was compared to other available tools (PHASTER, Prophinder and PhiSpy), using Sensitivity (Sn) tests and using the Positive Predictive Value (PPV). As reference for the tests, more than 80 manually annotated genomes were used, and on the PhageWeb analysis a Sn index was equal to 86.1% and the PPV of approximately 87%, while the second better tool presented Sn and PPV values of 83.3% and 86.5%, respectively. These indices allowed us to observe a greater precision in the regions identified by PhageWeb as compared to other prediction tools submitted to the same tests. Additionally, PhageWeb was faster than the other computational alternatives, decreasing the processing time to approximately one-eighth of the time required by the second better software and has its data integrated to biological databases. PhageWeb is freely available at http://computationalbiology.ufpa.br/phageweb.